AN INQUIRY INTO THE PROFESSIONAL IDENTITIES OF TWO ENGLISH TEACHERS IN AN INDONESIAN RURAL SCHOOL - Muthia Shahnaz, - (2022)
Teacher professional identity has become an increasingly popular research topic in understanding teachers' professionalism. However, research about professional identity, specifically on English language teachers in the Indonesian rural context, has not been much investigated. This study investigates how a rural school context shapes two rural teachers' professional identities. I employed a narrative research design and collected data through interviews, observations, and lesson plan analyses. The participants were two English teachers in a rural school located in Jambi Province. The findings indicated that both teachers' professional identities were shaped by the rural context and their experiences, emotions, beliefs, and knowledge. These components shaped the teachers' professional identities differently and influenced how each teacher approached their students. One tended to be a teacher who concerns more on a personal approach between student-teacher, and the other one concerns more on a student-motivating approach. Although the two teachers showed different identities and different ways of approaching their students, they both agreed that the students deserve a better education. The rural context has transformed both teachers into empathetic teachers willing to persevere for many years despite the challenges ahead. This study implied that rural teachers deserve to be more appreciated, be well paid, get sufficient facilities, and have good well-being because of the challenges they faced. Keywords: Narrative inquiry, rural schools, rural teachers, teacher professional identity